Implementation of a scoring system for assessing difficult cholecystectomies in a single center - Bulbuller, N; Ilhan, YS; Baktir, A; Kirkil, C; Dogru, O (Springer, 2006)
Purpose. Laparoscopic cholecystectomy (LC) is the treatment of choice for symptomatic cholelithiasis, but sometimes conversion to open cholecystectomy (OC) is necessary. The difficulty of LC or the risk of conversion to OC can be predicted by assessing some preoperative variables. We evaluated the efficacy of the risk score for conversion from laparoscopic to open cholecystectomy (RSCLO), which was recently developed by Kama et al. (Am J Surg 2001; 181:520), in a single center. Methods. We recorded the RSCLO values of 571 patients admitted to undergo LC in the Department of General Surgery, Firat University Hospital, between June 2001 and June 2004. Results. The mean RSCLO score of 19 patients who needed conversion to OC was significantly higher than that of the patients who underwent successful LC, at 16.2 (range, -9 to 41) vs -5.7 (range, -20 to 25) (P < 0.001). The RSCLO was well correlated with conversion to OC. The sensitivity and specificity rates for RSCLO determining the risk of conversion to OC were 100% and 96%, respectively, and its positive and negative predictive values were 43% and 100%, respectively. Conclusion. We think that RSCLO could be used to define the term difficult LC more accurately and assist in selecting the most appropriate operation.
Keywords: laparoscopy; cholecystectomy; conversion to open cholecystectomy; difficult cholecystectomy